Reinventar el lirismo: poéticas del yo y ruptura de los códigos de género en la poesía contemporánea (2015)
The richness of contemporary poetry lies in the plurality of literary languages that comprise it. However, one of the most significant trends, that which descends in direct line from the vanguard, the Brazilian Concretism and the latest generation of poets of the risk, supposes that the boldest poetry of our time has broken the gender codes, with the notion of the ego (hence with the notion of lyricism), with the communicative function (producer of sense) of the language, etc. So, it stops speaking of poetry to retake other terms as writings, transtexts, linguistic islands, etc. This paper aims, from the current contributions of American (Perloff, Hoagland, Swensen, Burt), French (Meschonnic, Caron, Maulpoix) and Hispanic criticism, to rethink the notion of lyricism and tell about the writings of the ego in the face of the limit of gender.